2019
DOI: 10.1002/jcb.28482
|View full text |Cite
|
Sign up to set email alerts
|

Integration of metabolomic and transcriptomic profiles to identify biomarkers in serum of lung cancer

Abstract: We used blood serum samples collected from 31 lung cancer (LC) patients and 29 healthy volunteers in this study. Levels of serum metabolites were qualitative quantified with gas chromatography-mass spectrometry (GC-MS), and the data were analyzed by partial least-squares discrimination analysis (PLS-DA). Based on the Kyoto Encyclopedia of Genes and Genomes database, we performed pathwaybased analysis utilizing metabolites presented at differential abundance between the LC serum samples and the normal healthy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…Metabolites are considered as both the building blocks of animal development and the regulators of animal health [27]. Metabolites in blood are reported to be highly responsive to environmental stress [28]. In the present study, twenty four metabolites whose concentrations were significantly affected by chronic HS were identified using the GC-MS-based metabonomic approach.…”
Section: Discussionmentioning
confidence: 98%
“…Metabolites are considered as both the building blocks of animal development and the regulators of animal health [27]. Metabolites in blood are reported to be highly responsive to environmental stress [28]. In the present study, twenty four metabolites whose concentrations were significantly affected by chronic HS were identified using the GC-MS-based metabonomic approach.…”
Section: Discussionmentioning
confidence: 98%
“…Metabolites are building blocks for growth and development; they are also key regulators and markers of animal health [87]. Blood metabolites are highly sensitive to environmental stress [88] and HS alters protein metabolism in a number of species [19,[89][90][91]. Metabolome analysis showed that several plasma metabolites were enriched in response to HS in both male and female groups, this included, creatinine, histidine, lysine, methionine, ornithine, serine, proline and pyruvate, while 4-aminobutryic acid, Creatine, Taurine and Urea concentration was lower post HS.…”
Section: Metabolome Regulation In Response To Heat Stressmentioning
confidence: 99%
“…Было установлено, что гиперурикемия является фактором риска развития и последующего тяжелого течения РЛ [9,10]. Считается, что пуриновые основания относятся к биомаркерам костных метастазов при РЛ, но их диагностическая и прогностическая значимость пока еще не определена [11].…”
Section: Introductionunclassified